Model pengaturcaraan gol untuk penjadualan kunjungan kempen politik: kajian kes di Kabupaten Kampar, Riau, Indonesia - Nasruddin Hassan,; Sri Basriati Mohammad Basir, (Penerbit ukm, 2009)

(untitled)
This paper discusses the development of a zero-one goal programming model to schedule a politician’s visit to his constituencies during the political campaign in Kabupaten Kampar, Riau, Indonesia. The visiting schedule has to be done in an efficient manner in order to have maximum exposure hence increasing his chance to win in the election. The model developed for this problem will be based on party policies. The politician must visit 20 constituencies in Kabupaten Kampar within a 14 day-period with certain conditions and requirements set by the party to be fulfilled. A feasible solution to the model is found using LINGO version 8.0